2013
DOI: 10.1371/journal.pone.0057600
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of HPV E6/E7 mRNA Assay in Women with Negative Colposcopy or CIN1 Histology Result: A Follow-Up Study

Abstract: Pap test, and especially HPV DNA test, identify a large group of women who do not have any clinically relevant lesions, i.e., CIN2+ (Cervical Intraepithelial Neoplasia grade 2 or worse), but who are at greater risk of getting lesions in the future. The follow up of these women needs new biomarkers with prognostic value. The objective of this study is to evaluate the prognostic value of E6/E7 mRNA over-expression assay (PreTect HPV-Proofer, Norchip) for 5 HR-HPV types (16, 18, 31, 33, and 45) for progression to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…Therefore, in our study, Pap test diagnosis was compared with the miRNAs expression for detecting missed high-grade lesions. Compared with previous literature data, the accuracy of our Pap test is slightly lower than that observed in cohort studies in which the gold standard was determined through follow up [51, 52]. This could be due to ascertainment biases in follow up studies or to lower progression of high grade lesion found in low grade cytology than those in high grade cytology or to low sensitivity of local cytology (at least in the distinction between low and high grade).…”
Section: Discussioncontrasting
confidence: 71%
“…Therefore, in our study, Pap test diagnosis was compared with the miRNAs expression for detecting missed high-grade lesions. Compared with previous literature data, the accuracy of our Pap test is slightly lower than that observed in cohort studies in which the gold standard was determined through follow up [51, 52]. This could be due to ascertainment biases in follow up studies or to lower progression of high grade lesion found in low grade cytology than those in high grade cytology or to low sensitivity of local cytology (at least in the distinction between low and high grade).…”
Section: Discussioncontrasting
confidence: 71%
“…The presence of both E6 and E7 mRNAs showed significant associations with the occurrence of upgraded abnormal cytology, the presence of E7 mRNA showed association without statistical significance, while positive E6 mRNA, HR-HPV DNA, or HPV 16/18 DNA showed no such trends ( Fig 4 ). Regarding follow-up study of HPV mRNA tests, the longitudinal studies have reported that positive mRNA at baseline is an excellent predictor for future development of CIN2+ or CIN3+ in referral or post-treatment populations [ 20 26 ]. Moreover, a recent longitudinal screening study has reported that the Aptima HPV test, which collectively detects E6/E7 mRNAs from 14 types of HR-HPV, has a similar sensitivity for detection of CIN2+ or CIN3+ and a significantly higher specificity than the HC2 test [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for detecting E6/E7 transcripts from oncogenic HPV types is to reduce the prevalence of clinically irrelevant lesions (thus implementing the specificity of cervical cancer screening), at the same time increasing the positive predictive value of DNA testing [ 17 ]. In summary, an E6/E7 -based test should be able to stratify the risk [ 18 ].…”
Section: Introductionmentioning
confidence: 99%